2015
DOI: 10.1039/c4cc09206f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent thiophene-based materials and their outlook for emissive applications

Abstract: Although thiophene-based materials are among the most widely studied conjugated materials for a number of technological applications, most discussions of emissive conjugated materials have focused on other systems, primarily due to the lower emission quantum yields of thiophene-based systems. Over the last decade, however, this has begun to change with the development of new highly emissive thiophene-based materials. In this review, we provide an overview of fluorescent thiophene-based materials and their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
101
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(108 citation statements)
references
References 157 publications
2
101
0
Order By: Relevance
“…As reported by Rasmussen and coworkers, oligothiophene materials have high quantum yields as well as significant solid-state emission. 23,24 End-capping DTP oligomers with thienyl groups produced red-shifted absorption and emission maxima in comparison to phenyl end-caps. 23 Yam et al .…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Rasmussen and coworkers, oligothiophene materials have high quantum yields as well as significant solid-state emission. 23,24 End-capping DTP oligomers with thienyl groups produced red-shifted absorption and emission maxima in comparison to phenyl end-caps. 23 Yam et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, conjugated materials have received ever increasing interest resulting from the fact that these systems combine the electronic and optical properties of classical inorganic semiconductors with many of the desirable properties of organic plastics [12,13]. This eventually resulted in the current field of organic electronics, with efforts focused on the development of technological applications such as sensors, electrochromic devices, organic photovoltaics (OPVs), organic light-emitting diodes (OLEDs), and field effect transistors (FETs) [12,13,14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…This short review aims to give a concise summary of polymers with side-chain thiophene-based functionalities, which can be prepared either by controlled polymerization techniques (e.g., ATRP, ROMP, and RAFT) or postpolymerization modification, and to introduce their properties and applications based on some recent or well-representative examples, which includes flexible polymer precursors to conjugated polymers, light-emitting polymeric materials as active components in electroluminescent devices, light-absorbing polymeric materials as active layers in photovoltaic cells, self-assembling amphiphilic block copolymers as functional nanomaterials, surface modification for novel hybrid nanocomposites, etc. Numerous reviews on main-chain thiophene-containing polymers can be found elsewhere [9,11,15,27,28]. This review will be limited to non-conjugated polymers with thiophene-based oligomers as pendant groups.…”
Section: Introductionmentioning
confidence: 98%